Microscopy detection and molecular characterisation of Giardia duodenalis infection in outpatients seeking medical care in Egypt - Elmahallawy, Ehab Kotb; Gareh, Ahmed; Ghallab, Marwa M. I.; Köster, Pamela C.; Dashti, Alejandro; Aboelsoued, Dina; Toaleb, Nagwa Ibrahim; Alzaylaee, Hind; Gonzálvez, Moisés; Saleh, Amira A.; Alhegaili, Alaa S.; Eldehn, Ahmed Fathy; et al. (Frontiers in Public Health, 2024)
Introduction: Giardiosis remains one of the most prevalent enteric parasitic infections globally. Earlier molecular-based studies conducted in Egypt have primarily focused on paediatric clinical populations and most were based on single genotyping markers. As a result, there is limited information on the frequency and genetic diversity of G. duodenalis infections in individuals of all age groups. Methods: Individual stool samples (n = 460) from outpatients seeking medical care were collected during January-December 2021 in Kafr El-Sheikh governorate, northern Egypt. Initial screening for the presence of G. duodenalis was conducted by coprological examination. Microscopy-positive samples were further confirmed by real-time PCR. A multilocus sequence typing approach targeted amplification of the glutamate dehydrogenase (gdh), beta-giardin (bg), and triose phosphate isomerase (tpi) genes was used for genotyping purposes. A standardised epidemiological questionnaire was used to gather basic sociodemographic and clinical features of the recruited patients.Results: Giardia duodenalis cysts were observed in 5.4% (25/460, 95% CI: 3.6-7.9) of the stool samples examined by conventional microscopy. The infection was more frequent in children under the age of 10 years and in individuals presenting with diarrhoea but without reaching statistical significance. Stool samples collected during the winter period were more likely to harbour G. duodenalis. All 25 microscopy-positive samples were confirmed by real-time PCR, but genotyping data was only available for 56.0% (14/25) of the isolates. Sequence analyses revealed the presence of assemblages A (78.6%, 11/14) and B (21.4%, 3/14). All assemblage A isolates were identified as subassemblage AII, whereas the three assemblage B sequences belonged to the sub-assemblage BIII. Patients with giardiosis presenting with diarrhoea were more frequently infected by the assemblage A of the parasite.Conclusions: This is one of the largest epidemiological studies evaluating G. duodenalis infection in individuals of all age groups in Egypt. Our molecular data suggest that G. duodenalis infections in the surveyed population are primarily of anthropic origin. However, because assemblages A and B are zoonotic, some of the infections identified can have an animal origin. Additional investigations targeting animal (domestic and free-living) and environmental (water) samples are warranted to better understand the epidemiology of giardiosis in Egypt.